0945 Sleep Complaints in Patients with Psychogenic Non-Epileptic Seizures. (12th April 2019) - Erickson, Joel; Fan, Jane; Roth, Heidi; Shin, Hae W; Wabulya, Angela; Ngo, Linh; Hinn, Albert; Vaughn, Bradley
Abstract: Introduction: Patients with psychogenic non-epileptic seizures (PNES) frequently complain of psychiatric and somatic symptoms including sleep issues. However, there is limited data characterizing sleep complaints in these PNES patients. Methods: Patients that were scheduled for admission to the epilepsy monitoring unit (EMU) for diagnostic video-EEG were asked to complete a variety of questionnaires including the Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), Quality of Life in Epilepsy Inventory-10-P (QOLIE-10-P), Patient Health Questionnaire (PHQ-4), and Morningness/Eveningness Questionnaire (MEQ). Patients were also asked to complete a sleep diary for the two weeks prior to their admission. Questionnaire results were analyzed using Pearson Product-Moment Correlation Coefficient to determine significant relationships (p<0.05) of sleep findings with those of mood and quality of life. Results: A total of 15 patients were identified as having PNES without epilepsy and were included in the analysis. Of PNES patients, the average age was 39 and 66% were female. 53% of patients had an elevated ISI and 60% of patients had an elevated ESS. Elevation of both ESS and ISI was seen in 26% of patients and elevation of both scores correlated with elevated PHQ-4 results (r=0.53, p=0.043). Quality of life also correlated with PHQ-4 (r=0.59, p=0.02). There was, however, no direct correlation between symptoms of insomnia or hypersomnia with quality of life. Conclusion: In our cohort, over three fourths (13 of 15) of our patients with PNES had sleep complaints, including one fourth having complaints of both insomnia and hypersomnia. Sleep complaints and poor quality of life both appear to independently correlate with increased severity of anxiety and depression. Insomnia is not correlated with poorer quality of life. Further characterization of sleep symptoms is needed for this population to help with determining a potential focus of treatment for common sleep complaints. Support (If Any)